Исследование закономерностей электронно-ионно-плазменного легирования стали - Колубаева Ю. А.; Иванов Ю. Ф. Юрий Федорович; Тересов А. Д.; Москвин П. В.; Shengzhi H.; Коваль Н. Н. Николай Николаевич (2011, 2011)
Заглавие с экрана